(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This scientific article examines the main causes and consequences of World War II as one of the most significant and destructive conflicts in world history. The study analyzes the political, economic, social, and ideological factors that led to the outbreak of the war, including the Treaty of Versailles, the rise of totalitarian regimes, economic instability, and failures of international diplomacy. Special attention is given to the global consequences of World War II, such as changes in the international political system, the emergence of new global powers, the establishment of international organizations, and long-term socio-economic impacts on participating states. The article aims to provide a comprehensive and balanced interpretation of World War II as a historical phenomenon whose effects continue to shape modern international relations.